Determining the role of fibrosis in hypertrophic cardiomyopathy. (April 2013) - Prinz, Christian; Farr, Martin; Laser, Kai Thorsten; Esdorn, Helmut; Piper, Cornelia; Horstkotte, Dieter; Faber, Lothar
Fibroblast activity within the heart may be considered a basically constructive process. Hyperactivity of fibroblasts, however, may result in the accumulation of extracellular matrix proteins with adverse effects on cardiac structure and function including electrical instability and increased risk of arrhythmogenic cardiac death. The detection of cardiac fibrosis by dedicated imaging techniques, mainly gadolinium-enhanced MRI, holds promise to refine patient management in a variety of cardiac conditions. This review aims to summarize the current knowledge regarding fibrosis in hypertrophic cardiomyopathy.